Q-switched thulium-doped fibre laser operating at 1900 nm using multi-walled carbon nanotubes saturable absorber - Saidin, Norazlina; Zen, Dess I.M.; Ahmad, Fauzan; Haris, Hazlihan; Ahmad, MT; Latiff, AA; Ahmad, Harith; Dimyati, K; Harun, Sulaiman Wadi (The Institution of Engineering and Technology (IET), 2014)
Simple, low-cost and stable passive Q-switched thulium-doped fibre lasers (TDFLs) operating at 1892.4 and 1910.8 nm are demonstrated using 802 and 1552 nm pumping schemes, respectively, in conjunction with a multi-walled carbon nanotubes (MWCNTs) saturable absorber (SA). The MWCNTs composite is prepared by mixing the MWCNTs homogeneous solution into a dilute polyvinyl alcohol (PVA) polymer solution before it is left to dry at room temperature to produce thin film. Then the film is sandwiched between two FC/PC fibre connectors and integrated into the laser cavity for Q-switching pulse generation. The pulse repetition rate of the TDFL configured with 802 nm pump can be tuned from 3.8 to 4.6 kHz, whereas the corresponding pulse width reduces from 22.1 to 18.3 μs as the pump power is increased from 187.3 to 194.2 mW. On the other hand, with 1552 nm pumping, the TDFL generates optical pulse train with a repetition rate ranging from 13.1 to 21.7 kHz with a pulse width of 11.5 7.9 μs when the pump power is tuned from 302.2 to 382.1 mW. A higher performance Q-switched TDFL is expected to be achieved with the optimisation of the MWCNT-SA saturable absorber and laser cavity.